CNT:TiO2-Doped Spiro-MeOTAD/Selenium Foam Heterojunction for High-Stability Self-Powered Broadband Photodetector - Yuxin Huang; Pengfan Li; Xuewei Yu; Shiliang Feng; Yanfeng Jiang; Pingping Yu (Nanomaterials)
Photodetectors are critical components in modern optoelectronic systems due to their extensive applications in information conversion and image storage. Selenium (Se), an element with a low melting point, a broad spectral response, and rapid response speed, exhibits a disadvantage of high optical reflectivity, which leads to a reduction in response. Spiro-MeOTAD, featuring controllable energy bands and facile processing, has its practical application limited by inadequate thermal and environmental stability. In this study, Spiro-MeOTAD-1 with enhanced stability was prepared through the optimization of dopants (Zn(TFSI)2 and CNT:TiO2) within Spiro-MeOTAD, to create a Se-F/Spiro-MeOTAD-1 heterojunction photodetector by subsequently compositing with selenium foam (Se-F). The self-powered device demonstrates exceptional photovoltaic performance within the wavelength range of 350–800 nm at 0 V bias, exhibiting a maximum responsivity of 108 mA W−1, a switching ratio of 5 × 103, a specific detectivity of 2.96 × 1012 Jones, and a response time of 20 ms/50 ms. The device also demonstrates elevated environmental stability pretreatment at 140 °C following a one-month period. The photodetection stability of the Se-F/Spiro-MeOTAD-1 flexible PD was demonstrated by its capacity to retain 76.3% of its initial light current when subjected to 70 bending cycles at 30°. This finding further substantiates the photodetection stability of the material under various bending conditions. Further verification of the applicability of Spiro-MeOTAD-1 in Se-based devices establishes a novel paradigm for designing photodetectors with enhanced performance and stability.